The significance of anti-streptokinase antibodies. - Lynch, M (1994)
Antibodies to streptokinase (SK) are widespread in the population, but reports of their effect on the action of SK are conflicting. Specific anti-SK IgG was purified from the sera of 10 patients, five with low titres of anti-SK IgG and five with high titres. The effect of increasing specific anti-SK IgG antibodies on the action of SK was evaluated in vitro using a fluorimetric assay for plasmin and by a fibrin plate lysis assay. The inhibition of SK by whole plasma from a further group of patients was also assessed by the fibrin plate assay. There was a positive correlation between the serum antibody concentration and the quantity of specific anti-SK eluted (r = 0.797; P < 0.005). The addition of specific anti-SK IgG caused a dose-related decrease in SK activity (fluorimetric assay r = -0.93; P = 0.02; fibrin plate assay r = -0.98; P < 0.001). The addition of patient plasma to the fibrin plate assay also resulted in decreased lysis, which was dependent upon antibody titre (r = -0.95; P < 0.0001). Significant in vitro reduction of the activity of SK by specific antibody was demonstrated, and this was similar with plasma containing comparable amounts of antibody. The findings suggest that treatment with SK would be unlikely to induce an effective thrombolytic state when antibody titres are high (such as those seen within 2 years of an initial dose of SK).